2021
DOI: 10.1155/2021/6667623
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Autof ms1000 and Bruker Biotyper MALDI-TOF MS Platforms for Routine Identification of Clinical Microorganisms

Abstract: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) is widely used in clinical microbiology laboratories because it is cost-effective, reliable, and fast. This study is aimed at comparing the identification performance of the recently developed Autof ms1000 (Autobio, China) with that of the Bruker Biotyper (Bruker Daltonics, Germany). From January to June 2020, 205 preserved strains and 302 clinical isolates were used for comparison. Bacteria were tested with duplicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(36 reference statements)
0
3
1
1
Order By: Relevance
“…In a previous validation study examining over 500 clinical isolates, Chudejova et al ( 2017 ) found automated sample preparation using the MALDI Colonyst robot improved overall identification scores and reduced error rates among both bacterial and fungal isolates when compared with manual sample deposition methods. While our study utilized only one MALDI-TOF MS instrument for MS-based colony identification, other instruments may perform at comparable levels (Pence et al 2014 ; Levesque et al 2015 ; Porte et al 2017 ; Brown-Elliott et al 2019 ; Park et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous validation study examining over 500 clinical isolates, Chudejova et al ( 2017 ) found automated sample preparation using the MALDI Colonyst robot improved overall identification scores and reduced error rates among both bacterial and fungal isolates when compared with manual sample deposition methods. While our study utilized only one MALDI-TOF MS instrument for MS-based colony identification, other instruments may perform at comparable levels (Pence et al 2014 ; Levesque et al 2015 ; Porte et al 2017 ; Brown-Elliott et al 2019 ; Park et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyeon Park et al compared the identification performance of the recently developed Autof ms1000 (Autobio Diagnostics Co., Ltd., Zhengzhou, China) with that of the Bruker Biotyper (Bruker Daltonics GmbH, Bremen, Germany). Studies reveal that both instruments showed comparable performance in the routine identification of clinical microorganisms [ 72 ]. Buchan et al, used the Mycobacterium Library v1.0 as an addition to the Mycobacterium specific spectral library used with the standard MALDI Biotyper software to identify the mycobacterium bacteria.…”
Section: Bacteria Identificationmentioning
confidence: 99%
“…方法无法满足快速鉴定的需求, 亟需建立针对临床标本或短时培养样本的直接检 测手段。MALDI-TOF MS 是目前可直接用于阳性血培养标本及尿液、脑脊液等 临床样本中病原体鉴定的优势技术之一 [12] ,通过缩减菌种培养耗费的时长,为 危重患者的诊断与治疗争取时间。 应用 MALDI-TOF MS 对血液培养物或尿液等临床样本进行检测时,需考虑 到血细胞或来自宿主与培养基的蛋白质对分析的影响,因此,适当的样品预处理 是准确鉴定病原体的前提。已有研究报道了不同处理方法的应用效果,其中, Sepsityper®试剂盒广泛应用于血源样品的前处理, 通过混合裂解缓冲液与血液培 养物以分解样品中的血液成分,随后通过高速离心收集细菌 [13] ;尿液前处理基 于逐步离心,洗涤,过滤和蛋白质提取的方案 [14] 相对成本较低,但标准化程度 有待提升,需要在进一步应用中优化出成本和效益两相平衡的前处理方法;为诊 断肺炎克雷伯菌引发的细菌性脑膜炎,有研究针对脑脊液样本进行离心洗涤,而 后利用乙醇-甲酸萃取法提取细菌内容物用于检测 [15] 。但应注意的是,在实践应 用中,临床样本中较低的细菌载量可能会限制这种方法的使用。 China) [16] 进行比较。多项研究评估了三种系统应用于细菌及真菌鉴定方面的性 能。Park 等 [17] 选取 205 个保存菌株和 302 个临床分离株作为测试样本,对 Autof ms 1000 与 Bruker Biotyper 系统进行性能比较,应用 16S rRNA 或 ITS 区序列分 析对鉴定结果存在差异的菌株进行鉴定。研究表明,保存菌株中,Autof ms 1000 与 Bruker Biotyper 在物种水平上的鉴定准确率分别达 98.5%、97.6%;在临床分 离株中则分别为 99.7%、 99.3%; Lin J N 等 [18] 比较了 VITEK MS 和 Bruker Biotyper 系统在鉴定临床分离株时的性能,发现两者对假单胞菌的准确鉴定率分别为 98.7%与 100%。上述研究提示三种系统应用于常规临床微生物鉴定时,相互之 间具备可比性。另外,一些研究通过联合商用 MALDI-TOF 系统与其他数据分 析系统, 进一步优化鉴定功能, 如 Wei J 等 [19] 开发了一种 Biotyper 与 ClinProTools 耐药相关生物标志物的特征性质谱峰检测等 [22] (见表 1)。…”
Section: -1-2 阳性血培养标本与尿液、脑脊液等临床样本的菌种鉴定 对于病程发展迅速、临床症状严重的细菌感染性疾病,常规标准的菌种培养unclassified